Limited interlaboratory comparison of Schmallenberg virus antibody detection in serum samples. (12th April 2014) - van der Poel, W. H. M.; Cay, B.; Zientara, S.; Steinbach, F.; Valarcher, J. F.; Bøtner, A.; Mars, M. H.; Hakze‐van der Honing, R.; Schirrmeier, H.; Beer, M.
Abstract : Eight veterinary institutes in seven different countries in Europe participated in a limited interlaboratory comparison trial to evaluate laboratory performances of Schmallenberg virus (SBV) antibody detection in serum. Seven different sheep sera and three different cattle sera were circulated, and all participating institutes were asked to test these sera using SBV antibody detection assay(s) in place in their laboratories. All laboratories within the trial performed a virus neutralisation test (VNT) as well as one or two ELISAs on all samples, and swiftly detected SBV antibodies using these assays. VNT was more sensitive in detecting SBV antibodies than several of the used ELISA assays. Based on the test results, one cattle and one sheep SBV antibody‐positive serum were selected to serve as reference sera, which now can be supplied to other laboratories on request.